Non-Traumatic Subdural Hemorrhage and Risk of Arterial Ischemic Events. Issue 5 (May 2020) - Murthy, Santosh B.; Wu, Xian; Diaz, Ivan; Parasram, Melvin; Parikh, Neal S.; Iadecola, Costantino; Merkler, Alexander E.; Falcone, Guido J.; Brown, Stacy; Biffi, Alessandro; Ch'ang, Judy; Knopman, Jared; et al.
Abstract : Background and Purpose—: The risk of arterial ischemic events after subdural hemorrhage (SDH) is poorly understood. This study aimed to evaluate the risk of acute ischemic stroke and myocardial infarction among patients with and without nontraumatic SDH. Methods—: We performed a retrospective cohort study using claims data from 2008 through 2014 from a nationally representative sample of Medicare beneficiaries. The exposure was nontraumatic SDH. Our primary outcome was an arterial ischemic event, a composite of acute ischemic stroke and acute myocardial infarction. Secondary outcomes were ischemic stroke alone and myocardial infarction alone. We used validated International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes to identify our predictor and outcomes. Using Cox regression and corresponding survival probabilities, adjusted for demographics and vascular comorbidities, we computed the hazard ratio in 4-week intervals after SDH discharge. We performed secondary analyses stratified by strong indications for antithrombotic therapy (composite of atrial fibrillation, peripheral vascular disease, valvular heart disease, and venous thromboembolism). Results—: Among 1.7 million Medicare beneficiaries, 2939 were diagnosed with SDH. In the 4 weeks after SDH, patients' risk of an arterial ischemic event was substantially increased (hazard ratio, 3.6 [95% CI, 1.9–5.5]). There was no association between SDH diagnosis and arterial ischemic events beyond 4 weeks. In secondary analysis, during the 4 weeks after SDH, patients' risk of ischemic stroke was increased (hazard ratio, 4.2 [95% CI, 2.1–7.3]) but their risk of myocardial infarction was not (hazard ratio, 0.8 [95% CI, 0.2–1.7]). Patients with strong indications for antithrombotic therapy had increased risks for arterial ischemic events similar to patients in the primary analysis, but those without such indications did not demonstrate an increased risk for arterial ischemic events. Conclusions—: Among Medicare beneficiaries, we found a heightened risk of arterial ischemic events driven by an increased risk of ischemic stroke, in the 4 weeks after nontraumatic SDH. This increased risk may be due to interruption of antithrombotic therapy after SDH diagnosis.